Classroom Practice OR Company Internships: Difficulty OR Comfort Zone? - Palomares, Ricard Calvo; Hernández, Juli A. Aguado; Signes, Enric Sigalat (Migration Letters, 2024)
This text presents the trend observed in development of the final projects of the Socio-Labour Auditing Techniques subject of the Degree in Labour Relations and Human Resources over the last six academic years. Since COVID-19, a large number of students opt to carry out their final practical based on the scenario provided by the teaching staff, despite the fact that they are encouraged to work with real cases in companies to perform the audits. On this basis, the question arises as to whether there is a process of complacency among students, a return to the "comfort zone", and whether this is a result of the pandemic situation and the difficulty of making contact with the business world. By integrating quantitative (survey of N=371 students) and qualitative (comments on the reasons for their choice) approaches, an attempt is made to resolve the question of whether it may be time to return to the previous proposals of gaining hands-on experience for the completion of final projects or if this change of approach is here to stay?